Women Organizations’ Activities on Community Development in Ikwerre Local Government Area of Rivers State, Nigeria - Aduwari, Sarah Ogah; Okwakpam, Iheanyi N. (International Journal of Global Community, 2018)
The study investigated the influence of women organisations on community development activities in Ikwerre local government area of Rivers State, Nigeria. The study adopted descriptive survey research design. Three research questions and three hypotheses were formulated for the study. The population of the study consisted of 10,150 women who are members of women organizations in the Ikwerre local government area of Rivers State, Nigeria. Through simple random sampling technique a total of 385 respondents were selected for the study. The research instrument used for the study was a questionnaire which was developed by the researchers and which yielded a reliability index of 0.71 and content validity of 0.90. The data generated from the study were analysed using descriptive statistics (mean and standard deviation) and Analysis of Variance (ANOVA) statistics. The findings revealed that women organisations play active roles in community development activities in the study area. The study recommended that the various governments (local, state and federal) should give matching grants and adequate funding to women organisations that are involved in community development activities.